Preparation, Structural Characterization and Antioxidant Activity of Extracellular Nanovesicles from Hericium erinaceus - Xueli YANG; Ben NIU; Hangjun CHEN; Weijie WU; Guannan WANG; Xiangjun FANG; Honglei MU; Haiyan GAO (Shipin gongye ke-ji)
Objective: To optimize the preparation method of Hericium erinaceus-derived extracellular nanovesicles and investigate their antioxidant activity and protective effect against oxidative damage in Caco-2 cells. Methods: Hericium erinaceus-derived extracellular nanovesicles (HEDENVs) were isolated from fresh Hericium erinaceus by ultracentrifugation and sucrose gradient ultracentrifugation. The optimal extraction process of HEDENVs was optimized by one-way test and response surface test, while the particle size, Zeta potential, and morphology of HEDENVs were characterized by a laser particle size instrument and transmission electron microscope. Lipidomics and proteomics analysis of HEDENVs was performed by liquid chromatography-mass spectrometry. The in vitro antioxidant activity of HEDENVs was evaluated by determining the DPPH, ABTS+, and O2− radical scavenging capacity. A Caco-2 cell oxidative stress damage model was created using H2O2, and changes in ROS content in cells were measured using laser confocal microscopy. Results: The optimal extraction process of HEDENVs was the 25% interface of the sucrose concentration, centrifugation time was 2 h, and centrifugal speed was 86000 r/min, at which the concentration of HEDENVs was 402.24 μg/mL. HEDENVs were nanovesicles with a lipid bilayer membrane, the particle size was 110.7±16.9 nm, PDI=0.551, and the Zeta potential was −14.2 mV. Based on the analysis of lipidomics and proteomics, 346 lipids species and 52 proteins were identified in HEDENVs. The results of in vitro antioxidant test showed that the scavenging rate of 400 μg/mL HEDENVs for DPPH free radical was 94.79%, the scavenging rate for ABTS+ free radical was 96.67%, and the scavenging rate for O2− free radical was 96.83%. An oxidative damage model in Caco-2 cells was established by H2O2, HEDENVs could significantly reduce the production of ROS in damaged cells. Conclusion: It showed that HEDENVs had certain antioxidant activity in various antioxidant experiment.